Antifungal activity and shelf life extension of loaf bread produced with sourdough fermented by Lactobacillus strains. Issue 10 (21st July 2019) - Luz, C.; D'Opazo, V.; Mañes, J.; Meca, G.
Abstract: The objective of this study was to evaluate a water‐soluble extract from sourdoughs fermented with the lactic acid bacteria (LAB) for antifungal reflect on loaf bread. The extracts produced by Lactobacillus plantarum CECT 749 and L. bulgaricus CECT 4005 were effective against strains of Fusarium spp., Penicillium spp., and Aspergillus spp ., with minimum inhibitory concentration ranging from 1.6 to 200 mg/ml and minimum fungicidal concentration from 1.6 to 400 mg/ml. LC‐ESI‐MS‐TOF was used to analyze the antimicrobial compounds. Several antimicrobial phenolic acids were found. Fermented sourdoughs used for the production of loaf bread produced a reduction of fungal growth in relation on the sourdough control and improved to the shelf life of 1 to 2 days compared to control bread with 0.2% calcium propionate. Therefore, LAB are an alternative to synthetic compounds for decreasing fungal contaminants and prolonging the shelf life of food. Practical applications: This study presents the importance of sourdough fermented by Lactobacillus plantarum spp. and the production during the fermentation of bioactive metabolites with antifungal activity. When applied in the preparation of bread, it is able to increase the useful life of the bread and its efficiency can be compared to that of calcium propionate. It is thus an alternative to synthetic compounds for decreasing fungal contaminants and prolonging the shelf life of food.